IMPLEMENTASI FILTERING MAC ADDRESS MENGGUNAKAN FITUR HOTSPOT DENGAN MIKROTIK PADA PT PERTAMINA DRILLING SERVICE INDONESIA JAKARTA - Noviar Armanda Nurdin; Septian Ardiansyah (LPPM Nusa Mandiri, 2018)
Pertamina Drilling Service Indonesia Jakarta which is engaged in the exploration and exploitation of oil and gas drilling. PT. PDSI Jakarta implements WLAN technology in its company because this network is so compatible that makes it easy for its employees to carry out work activities such as processing data, sharing resources and looking for other important information. There are several main problems faced by clients and problems in computer networks including PT. PDSI Jakarta uses the Captive Portal on WLAN networks, so users can still log in via several different devices in the area. The occurrence of IP conflicts on the client, the antivirus used by the client still uses the default antivirus from Windows, the Windows antivirus defender. Which is where there is no additional firewall to strengthen network security on the client. The purpose of the study is so that users cannot log in with different devices, fix IP conflicts, use the latest anti-virus.